Observation of B[bar]→D(∗)π+π-l[iota]-v[bar] decays in e+e- collisions at the [upsilon](4S) resonance - Lees, Jean-Pierre; Adametz, Aleksandra; Uwer, Ulrich (Physical review letters, 2016)
We report on measurements of the decays of ¯B mesons into the semileptonic final states ¯B→D(*)π+π−ℓ−¯ν, where D(*) represents a D or D∗ meson and ℓ− is an electron or a muon. These measurements are based on 471×106 B¯B pairs recorded with the BABAR detector at the SLAC asymmetric B factory PEP-II. We determine the branching fraction ratios R(*)π+π−=B(¯B→D(*)π+π−ℓ−¯ν)/B(¯B→D(*)ℓ−¯ν) using events in which the second B meson is fully reconstructed. We find Rπ+π−=0.067±0.010±0.008 and R∗π+π−=0.019±0.005±0.004, where the first uncertainty is statistical and the second is systematic. Based on these results and assuming isospin invariance, we estimate that ¯B→D(*)ππℓ−¯ν decays, where π denotes either a π± and π0 meson, account for up to half the difference between the measured inclusive semileptonic branching fraction to charm hadrons and the corresponding sum of previously measured exclusive branching fractions.
Im Titel sind "iota" und "upsilon" als griechischer Buchstaben dargestellt
Im Titel ist das "v" mit einem Oberstrich dargestellt
Im Titel sind die Zeichen "+", "-" und "(*)" hochgestellt
Gesehen am 14.07.2020